Construção e validação do instrumento LAND-IES COVID-19 para avaliar a ansiedade em docentes universitários - Freitas, Poliana de Lima (2022)
Anxiety is a general term that characterizes symptoms of several disturbing characteristicsthat they treat, whose best known diseases are nervousness, fear, apprehension and worry in the face of the unknown, becoming a mental illness when it occurs in excess and becomes a limiting factor. of everyday life. Some variables can be triggering factors, such as the performance of work functions. Currently, the health scenario in Brazil and in the world is a challenging factor for mental health, since the world is in the midst of a pandemic by the SarsCov2 virus, which can cause Severe Acute Respiratory Syndrome (COVID-19), since 2019 and development of activities in a home office model (work at home). One of the most efficient tools for surveying the population incidence is the construction of well-founded and validated information, which collects worthy nature to corroborate with research. The construction of an important term is carried out following some steps described in the steps, although it is not a process with an already established term. The validation of such instrument takes place through the careful analysis of a Committee of Judges, and a subsequent semantic analysis carried out through the application of the instrument in a small portion of the selected sample. Therefore, the present work aimed at the construction and validation of a questionnaire, which is reliable for all the objectives it proposes, which is the evaluation of anxiety symptoms in teachers. To carry out this research, an exhaustive study was carried out in the literature that discusses the construction of questionnaires in order to follow the most recommended processes to arrive at the construction of a quality instrument. The search platforms for the construction of the questionnaire were the PePSIC, SciELO, Google Escolar and PUBMED databases. The research result culminated in the construction of the LANDIES COVID-19 instrument, a self-administered virtual questionnaire adapted to the Google Forms platform. Then, the instrument was analyzed by 5 judges selected for their titles, as well as experience in the area and the construct chosen here. The evaluation of the committee of judges took place through an instrument developed for this evaluation of all domains, as well as the items present in the instrument, through the selection of agreement. Then, the analysis of the Content Validity Coefficient (CVC) was performed. All domains, items and the instrument in general obtained CVC> 0.80, thus considered adequate and maintained in the instrument with minor changes suggested by the judges. For the pre-test stage, the instrument was answered and suggestions for improvements made by about 11 professors working at the FASTECH/Sinop-MT higher education institution. The research was concluded with the final version of the reliable and relevant instrument, which contains 81 questions, 65 of which are multiple choice, mutually exclusive, 9 essay questions as a complement to other questions and 7 scaled Likert-type questions, divided into 4 sections. Once its construction and validation is completed, it is ready to be applied to the population in future research.